In-Hospital Management and Outcomes After ST-Segment–Elevation Myocardial Infarction in Medicaid Beneficiaries Compared With Privately Insured Individuals. Issue 1 (January 2019) - Patel, Nirav; Gupta, Ankur; Doshi, Rajkumar; Kalra, Rajat; Bajaj, Navkaranbir S.; Arora, Garima; Arora, Pankaj
Abstract : Background: Medicaid expansion among previously uninsured individuals has led to improved healthcare access. However, considerably lower reimbursement rates of Medicaid have raised concerns on the unintended consequence of lower utilization of life-saving therapies and inferior outcomes compared with private insurance. We examined the rates of revascularization and in-hospital mortality among Medicaid beneficiaries versus privately insured individuals hospitalized with ST-segment–elevation myocardial infarction (STEMI). Methods and Results: We queried the National Inpatient Sample from 2012 to 2015 for STEMI hospitalizations with Medicaid or private insurance as primary payer. Hospitalizations with the following criteria were excluded: (1) age <18 or ≥65 years, (2) transfer to another acute care facility, and (3) left against medical advice. Outcomes were compared in propensity score–matched cohort based on demographics, socioeconomic status (income based), clinical comorbidities, including drug and alcohol use, STEMI acuity (cardiac arrest and cardiogenic shock), and hospital characteristics. A total of 42 645 and 171 545 STEMI hospitalizations were identified as having Medicaid and private insurance, respectively. In unadjusted analyses, Medicaid beneficiaries with STEMI had lower rates of coronary revascularization (88.9% versus 92.3%; odds ratio, 0.67; 95% CI, 0.65–0.70) and higher rates of in-hospital mortality (4.9% versus 2.8%; odds ratio, 1.81; 95% CI, 1.72–1.91) compared with privately insured individuals ( P <0.001 for both). In propensity-matched cohort of 40 870 hospitalizations per group, similar results for lower rates of revascularization (89.1% versus 91.1%; odds ratio, 0.80; 95% CI, 0.76–0.84) and higher in-hospital mortality (4.9% versus 3.7%; odds ratio, 1.35; 95% CI, 1.26–1.45) were observed in Medicaid compared with private insurance, despite extensive matching ( P <0.001 for both). Conclusions: Medicaid beneficiaries with STEMI had lower rates of revascularization, although small absolute difference, and higher in-hospital mortality compared with privately insured individuals. Further studies are needed to identify and understand the variation in STEMI outcomes by insurance status. Abstract : Supplemental Digital Content is available in the text.